THE POLITICAL ECONOMY OF PUBLIC UTILITIES : A Study of the Indian Power Sector - Kannan, KP and Vijayamohanan Pillai, N (Centre for Development Studies-WP316, 2001)
In this paper, we attempt at an analysis of the political economy of the Indian power sector with special reference to Kerala in the light of a generic model of the political economy of public utilities we develop in the first part of the paper. The model seeks to explain the political economy of the rent seeking drives in a non-Smithian imperfect regime of self-interest maximisation, with a regulatory structure of the public utility described in a framework of the principal-agent relationship. In contrast to the usual neo-classical monolithic representation of principal and agent, we characterise each entity in a Marxian-Kaleckian vein, as a composite set of conflicting sectional interests. This helps us develop a comprehensive perspective of the politico-economic implications of the relationship among the public, government and utility. Based on this generic model, we seek to analyse, in the second part of the paper, the political economy of the power sector in India, with emphasis on Kerala. We also attempt, wherever possible, to estimate the costs of corruption involved in the administration of the power sector.